2022
DOI: 10.3390/molecules27238333
|View full text |Cite
|
Sign up to set email alerts
|

Novel Push-Pull Benzodithiophene-Containing Polymers as Hole-Transport Materials for Efficient Perovskite Solar Cells

Abstract: Donor-acceptor conjugated polymers are considered advanced semiconductor materials for the development of thin-film electronics. One of the most attractive families of polymeric semiconductors in terms of photovoltaic applications are benzodithiophene-based polymers owing to their highly tunable electronic and physicochemical properties, and readily scalable production. In this work, we report the synthesis of three novel push–pull benzodithiophene-based polymers with different side chains and their investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Synthesis of benzodithiophene-based compounds 10-13 was described in details in our previous work. [21] Small molecules were purified by standard column chromatography using silica and a mixture of hexane and toluene as eluent. Finally, all compounds were precipitated from toluene with cold ethanol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of benzodithiophene-based compounds 10-13 was described in details in our previous work. [21] Small molecules were purified by standard column chromatography using silica and a mixture of hexane and toluene as eluent. Finally, all compounds were precipitated from toluene with cold ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of benzodithiophene‐based compounds 10 – 13 was described in details in our previous work [21] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monomer BDT was obtained by the method reported previously. 22 The detailed synthetic procedures and characterization are described in the Experimental section (NMR spectra are presented in Fig. S1-S12, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, three (X-ADA) n benzodithiophene-containing ( BDT ) polymers have been designed and investigated as HTMs in n–i–p PSCs. 22 We showed that the introduction of triisopropylsilyl side chains into the benzodithiophene X block provides better film-forming properties and increased charge carrier mobility of the resulting polymer compared to the polymeric HTMs consisting of alkyl- or alkoxy-substituted BDT blocks. The best cells with the BDT -based HTM yielded a PCE of ca.…”
Section: Introductionmentioning
confidence: 93%